2020
DOI: 10.1186/s13584-020-00418-w
|View full text |Cite
|
Sign up to set email alerts
|

Income assurances are a crucial factor in determining public compliance with self-isolation regulations during the COVID-19 outbreak – cohort study in Israel

Abstract: Background The outbreak of a new Coronavirus disease (COVID-19) poses dramatic challenges to public health authorities worldwide. One measure put in place to contain the spread of the disease is self-quarantine of individuals who may have been exposed to the disease. While officials expect the public to comply with such regulation, studies suggest that a major obstacle to compliance for self-quarantine is concern over loss of income or employment due to the prolonged absence from work. Methods A cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…In addition, respondents with a decreased income expectation of more than 3000 Chinese yuan accounted for 20% of the total number, and from the perspective of occupational characteristics, private owners, private enterprises and freelancers believed that their income levels were most negatively affected by COVID-19. This finding is consistent with Bodas [ 37 ] and Sandeep [ 38 ] who argued for a relatively short-term impact of the pandemic on people’s expected income.…”
Section: Resultssupporting
confidence: 92%
“…In addition, respondents with a decreased income expectation of more than 3000 Chinese yuan accounted for 20% of the total number, and from the perspective of occupational characteristics, private owners, private enterprises and freelancers believed that their income levels were most negatively affected by COVID-19. This finding is consistent with Bodas [ 37 ] and Sandeep [ 38 ] who argued for a relatively short-term impact of the pandemic on people’s expected income.…”
Section: Resultssupporting
confidence: 92%
“…[23][24][25] The Arab minority traditionally supports leftwing parties and its sectorial parties have never joined the coalition in the Israeli governments. 22,24,26 A plethora of studies have pointed out various factors associated with compliance with preventive health measures during the COVID-19 pandemic 1,[27][28][29][30][31][32][33] and in previous ones. 11,[34][35][36][37][38][39][40] Such factors include demographic factors such as gender, age and education.…”
Section: Introductionmentioning
confidence: 99%
“…1,11,27,28 These studies have also indicated that psychological and psychosocial factors, including emotional distress, risk perceptions and perceptions about the efficacy of the instructions and one's ability to comply with them are all positively associated with compliance. 1,11,27,29,[35][36][37]41 Additional factors that affect compliance are political and civic attitudes such as political orientation, trust in government and the health authorities, legal and moral norms, as well as economic conditions and considerations. 1,29,38,39,[42][43][44][45][46] Moreover, studies have found complex relationships between the factors associated with compliance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as in 2019 almost none of the articles based on surveys looked at changes over time. In fact, out of 22 articles using survey data, only two of them used surveys to look at changes over time [ 13 ] [ 14 ], and only one of them made secondary use of data from an existing survey [ 14 ].…”
Section: Appendixmentioning
confidence: 99%